Host‐induced gene silencing – mechanisms and applications. Issue 1 (2nd May 2021) - Koch, Aline; Wassenegger, Michael
Summary: Host‐induced gene silencing (HIGS) technology has emerged as a powerful alternative to chemical treatments for protecting plants from pathogens or pests. More than 170 HIGS studies have been published so far, and HIGS products have been launched. First, we discuss the strengths and limitations of this technology in a pathosystem‐specific context. Next, we highlight the requirement for fundamental knowledge on the molecular mechanisms (i.e. uptake, processing and translocation of transgene‐expressed double‐stranded RNAs) that determine the efficacy and specificity of HIGS. Additionally, we speculate on the contribution of host and target RNA interference machineries, which may be incompatible depending on the lifestyle of the pathogen or pest. Finally, we predict that closing these gaps in knowledge will lead to the development of novel integrative concepts, precise risk assessment and tailor‐made HIGS therapy for plant diseases.